Spontaneous Intracerebral Heamorrhage at Turku University Hospital and Applications of Surgical Mini-Invasive Operation Technique : A Clinical Retrospective Study - Lehto, Sami (My University, 2023)
Background: Intracerebral haemorrhage (ICH) is a great cause of mortality and morbidity globally. However, there has been little progress in improving survival and functional outcome. Several large- scale randomized trials have compared either open surgery (STICH I and II) or stereotactic catheter thrombolysis (MISTIE-III), but they have been neutral in their primary outcome, good functional recovery. Although in MISTIE-III they did achieve a lower mortality while increasing the amount of very poor functional outcomes. Recently published post-hoc analyses have suggested a potential functional benefit to surgical intervention with correct patient selection and adequate surgical per- formance. We sought to characterise spontaneous ICHs treated at Turku University Hospital to es- timate the incidence of ICHs and characterize patients that potentially for benefit from surgical in- tervention. Method: This was a retrospective clinical study, which identified 596 patient cases of ICH treated during the years 2018 and 2019 in Turku University Hospital. Of these 287 were identified as being supratentorial spontaneous ICHs and were further analysed as potential candidates for mini-invasive catheter thrombolysis as described in MISTIE-III protocol. For continuous variables, two sample t- test was used to compare means of modified Rankin scale (mRS) groups with Satterthwaite correc- tion as required. Chi-square test or Fisher’s exact test were used for comparing proportions between or among categorical variables. Results: Incidence of supratentorial of ICH was 29.9 per 100 000 persons per year and the inci- dence of ICH patients that met MISTIE-III criteria was 2.7 per 100 000 persons per year. From 287 patients, 26 patients met criteria for MISTIE-III. They were likelier to have an unfavourable func- tional outcome (mRS 4-6, p = .0049) and had on average larger ICHs by volume, 64.2 ml (SD 38.4 ml) compared to 27.5 ml (SD 44.2 ml) in non-eligible patients (p <.0001). There were no statistically significant demographic differences between MISTIE-III eligible and ineligible patients. Conclusion: There are a small, but significant number of ICHs amenable to surgical intervention based on criteria from MISTIE-III and its post-hoc analyses. This would be sufficient to enable routine surgical intervention once definite patient selection and surgical technique have been estab- lished.
Keywords: intracerebral haematoma, mini-invasive, MISTIE-III, neurovascular surgery